Experimental Research on the Wearability,Corrosion Resistance,and Life Assessment of an Aluminum Alloy Bridge Deck - 李吉勤 班慧勇 石永久 王元清 张振学 (Tsinghua science and technology, 2010)
High-performing wearability and corrosion resistance are required for an exposed aluminum alloy bridge deck,but existing experimental research remains limited.In this paper,feasible test methods are proposed based on an experimental study on the wearability and corrosion resistance of the aluminum alloy bridge deck of the Bengbu Bridge in Tianjin,China.The line friction test of standard specimens was adopted,and the aluminum alloy bridge deck＇s wearability was calculated.The electrochemical test was conducted to measure the corrosion rate and morphology characteristics of specimens that were corroded in various solutions that simulated the atmospheric environment.The test results show that the wearability and corrosion resistance of the aluminum alloy bridge deck are sufficient and met the project＇s requirements.The test methods proposed have practical significance for future engineering research,and the test results are useful for other engineering applications of aluminum alloys.